Accuracy of Miniscrew Implant Placement With a 3-Dimensional Surgical Guide - Eduardo Yugo Suzuki (2018)
Purpose: Deviation in the trajectory during drilling or tapping of miniscrew implants increases the risks of root injury. The purposes of this study were to assess the accuracy of miniscrew placement into the dentoalveolar bone, aided by a 3-dimensional (3D) surgical guide, and to compare the results with those from conventional procedures. Materials and Methods: A total of 220 miniscrews implanted, aided by a 3D surgical guide (n = 180), a conventional wire guide (n = 20), or no surgical guide (n = 20), were retrospectively examined in relation to the accuracy of placement. Coordinates, distances, and angles of the superimposed images of the planned and the correspondent implants were assessed and analyzed by 1-way analysis of variance. Results: The results demonstrate that using the 3D surgical guide produced a significantly smaller variation between the planned and actual implant positions at the miniscrew head and tail (0.6 ± 0.5 mm [mean ± standard deviation] and 2.0 ± 0.4 mm) compared with the wire guide (1.0 ± 0.4 mm and 5.3 ± 1.1 mm) and no guide (3.6 ± 1.7 mm and 10.5 ± 3.5 mm). The accuracy of placement was significantly improved with the 3D surgical guide (1.8 ± 0.9°) compared with the wire guide (16.9 ± 2.6°) and no guide (21.2 ± 2.9°). Conclusions: The 3D surgical guide provides a precise method for miniscrew placement into the dentoalveolar bone. The accurate insertion of miniscrews using the 3D surgical guide allows orthodontists to precisely transfer the radiographic information from preoperative planning to the surgical site, thus minimizing the risks of root injury. © 2008 American Association of Oral and Maxillofacial Surgeons.